Estudio de factibilidad de un plan de contingencia ante una posible suspensión de energía eléctrica en la ciudad de baños frente a un desastre natural a nivel de 13.8 kv en la Empresa Eléctrica Ambato Regional Centro Norte S.A - Guacho Vizuete, Juan Pablo (2015)
This researching work, "Feasibility Study of an Emergency Plan to face a possible stoppage of the Electric Power in the City of Baños, for dealing a natural disaster at a level of 13.8 KV in the Empresa Eléctrica Ambato S.A. of Centre North Region", is based on a meticulous analysis of the potential risks that the electrical systems of primary distribution of Baños city may be exposed in case of a full or partial eruption of Tungurahua Volcano. In case of this, some important steps, prompt actions and maintaining a continuous electrical service in evacuation points located by the National Secretariat for Risk Management, Civil Defense Organization must be done....